Fertility decision of Iranian women during the COVID-19 pandemic and home quarantine: A cross-sectional study in Iran - Afshari, Poorandokht; Abedi, Parvin; Beheshtinasab, Maryam (Frontiers in Psychology, 2022)
Background: Fertility decision is defined as the mutual decision of partners toward having children, which may be equally controlled by the two partners or dominantly powered by the female partner. This study aimed to evaluate fertility decision of women during the COVID-19 pandemic in Iran. Methods: This cross-sectional study was conducted on 600 women (300 pregnant and 300 non-pregnant) during the COVID-19 pandemic. A demographic questionnaire and the Attitudes toward Fertility and Childbearing Scale were used to collect the data. Independent t-test, Chi-square test, and logistic regression were used for analysing data. Results: The mean ± SD age of participants with negative and positive attitude toward fertility was 28.96 ± 5.88 and 28.39 ± 6.2 respectively. Almost half of the studied women postponed their pregnancy to after the pandemic. The total score of fertility decision in women with positive attitudes toward fertility was 95.43± 18.51 compared to 46.73 ± 17.2 in women with negative attitudes toward fertility (p<0.0001). None-employed women had 0.595 times the odds of having a positive attitude toward fertility (95% CI: .423-.836). Women who were not pregnant had 1.5 times the odds of having a positive attitudes toward childbearing (95% CI: 1.067-2.112). In addition, women who were hospitalized during the pandemic had 0.520 times the odds of having a positive attitude toward fertility (95% CI: 0.342-0.790). Conclusion: The results of this study showed that half of the women postponed their pregnancy to after the pandemic. Also, employed women, women who were not pregnant, and women who were not hospitalized during pandemic were more likely to have positive attitudes toward fertility during the COVID-19 pandemic. Policymakers should devise some strategies to clarify the benefits and harms of pregnancy during crises such as COVID-19 pandemic.